Physiologically‐based pharmacokinetic modeling of immunoglobulin and antibody coadministration in patients with primary human immunodeficiency - Sara N. Salerno; Rong Deng; Tarundeep Kakkar (Wiley, 2022)
Abstract Intravenous immunoglobulin (IVIG) (2000 mg/kg) increased the clearance of the mouse monoclonal antibody 7E3, directed against platelet integrin IIb/IIIa (alpha IIb beta 3, CD41/CD61) in rodents. We wanted to investigate the effect of IVIG on clearance of monoclonal antibodies in humans as there is extremely limited data regarding this interaction in the literature. Using the tyrosine protein kinase KIT anti‐cluster of differentiation 117 (c‐Kit) humanized monoclonal antibody (JSP191) as a case study, we used physiologically‐based pharmacokinetic (PBPK) modeling to evaluate the pharmacokinetic interaction between monoclonal antibodies and IVIG at doses (300-600 mg/kg) administered to patients with primary human immunodeficiency (PI). We first characterized the interaction between monoclonal antibodies and IVIG in PK‐Sim®/MoBi® using published literature data, including the following: IVIG plus 7E3 in mice and rats and IVIG plus the human anti‐C5 monoclonal antibody tesidolumab in adults with end‐stage renal disease. We next developed a PBPK model using digitized data for JSPI91 alone in older adults with myelodysplastic syndrome and acute myeloid leukemia and in pediatric patients with severe combined immunodeficiency (SCID). Finally, we simulated the impact of IVIG (300-2000 mg/kg) coadministration with JSP191 on the area under the curve of JSP191 in patients with SCID. Model predictions were within 1.5‐fold of observed values for 7E3 plus IVIG and tesidolumab plus IVIG as well as for JSP191 administered alone. Based on our simulations, IVIG doses ≥500 mg exceeded the 80%-125% no‐effect boundaries. IVIG treatment with monoclonal antibodies in patients with PI may result in a clinically significant interaction depending on the IVIG dose administered and the exposure-response relationship for the specific monoclonal antibody.